Recomendaciones para el manejo de la faringoamigdalitis aguda del adulto() - Cots, Josep M. (Semergen, 2015)
Acute pharyngitis in adults is one of the most common infectious diseases seen in general practitioners’ consultations. Viral aetiology is the most common. Among bacterial causes, the main agent is Streptococcus pyogenes or group A β-haemolytic streptococcus (GABHS), which causes 5%-30% of the episodes. In the diagnostic process, clinical assessment scales can help clinicians to better predict suspected bacterial aetiology by selecting patients who should undergo a rapid antigen detection test. If these techniques are not performed, an overdiagnosis of streptococcal pharyngitis often occurs, resulting in unnecessary prescriptions of antibiotics, most of which are broad spectrum. Consequently, management algorithms that include the use of predictive clinical rules and rapid tests have been set up. The aim of the treatment is speeding up symptom resolution, reducing the contagious time span and preventing local suppurative and non-suppurative complications. Penicillin and amoxicillin are the antibiotics of choice for the treatment of pharyngitis. The association of amoxicillin and clavulanate is not indicated as the initial treatment of acute infection. Neither are macrolides indicated as first-line therapy; they should be reserved for patients allergic to penicillin. The appropriate diagnosis of bacterial pharyngitis and proper use of antibiotics based on the scientific evidence available are crucial. Using management algorithms can be helpful in identifying and screening the cases that do not require antibiotic therapy.